Pre-stroke Physical Activity and Cerebral Collateral Circulation in Ischemic Stroke: A Potential Therapeutic Relationship? - Hung, Stanley Hughwa; Kramer, Sharon; Werden, Emilio; Campbell, Bruce C. V.; Brodtmann, Amy (Frontiers in Neurology, 2022)
Favourable cerebral collateral circulation contributes to preventing penumbral tissue from progressing to infarction and is associated with positive clinical outcomes after stroke. Given its clinical importance, improving cerebral collateral circulation is considered a therapeutic target to reduce burden after stroke. We provide a hypothesis-generating discussion on the potential association between pre-stroke physical activity and cerebral collateral circulation in ischaemic stroke. The recruitment of cerebral collaterals in acute ischaemic stroke may depend on anatomical variations, capacity of collateral vessels to vasodilate, and individual risk factors. Physical activity is associated with improved cerebral endothelial and vascular function related to vasodilation and angiogenic adaptations, and risk reduction in individual risk factors. More research is needed to understand association between cerebral collateral circulation and physical activity. A presentation of different methodological considerations for measuring cerebral collateral circulation and pre-stroke physical activity in the context of acute ischaemic stroke is included. Opportunities for future research into cerebral collateral circulation, physical activity, and stroke recovery is presented.